ANALISIS PERAN PT. BANK MANDIRI (PERSERO) TBK. UNIT MANDIRI MITRA USAHA DALAM PEMBERIAN KREDIT USAHA RAKYAT PADA USAHA MIKRO DI SAMARINDA. - Umar Hi Salim (RJABM (Research Journal of Accounting and Business Management), 2018)
The purpose of this paper is to identify and analyze the implementation of Uhasa Rakyat Credit from PT. Bank Mandiri (Persero) Tbk. Mandiri Mitra Business Unit in developing micro and small business. Based on the research, the number of samples taken as many as 65 debtors with the amount of credit Rp 20.000.000, - up to Rp 50.000.000, - and indicators to develop small and micro businesses, the debtor (customers), namely; capability of initial capital owned, production activities (business) undertaken, sales turnover obtained, and net profit earned. The result shows that the difference between the average value before and after obtaining credit is 3.97 (12.60 - 8.63), this is quite big. The difference in the average value of this very large, then the debtor who before getting a loan as additional capital to develop business and increase income. The result of t test analysis for income difference for debtor before and after obtaining credit, where t value counted as -16,0145, while t value of table shows 2,000, it shows that t empirical (count) bigger when compared with t table or -16.0145> 2.000 which means there is a difference of income between the debtor after receiving credit assistance with the debtor who before getting credit assistance from PT. Bank Mandiri (Persero) Tbk. Thus, the proposed hypothesis can be proven and true, that there is a difference between the debtor who after receiving credit assistance with before getting credit assistance.